Study of the Determinants of Condom Use among Students at the University of Lake Tanganyika in Burundi. A Cross-sectional Analytical Study - Nkurunziza Nice Noella; Jean Berchmans Niyonzima; Rachid Aboutaieb (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Sexual and reproductive health among youth is a major public health issue in sub-Saharan Africa. This population group, undergoing biological, psychological, and social transitions, is particularly vulnerable to sexually transmitted infections (STIs), HIV/AIDS, and unintended pregnancies. Several interrelated factors exacerbate this vulnerability: early sexual initiation, lack or inadequacy of structured sex education, stigmatization of preventive behaviors, and unequal access to protective means, particularly condoms. Despite efforts by health authorities and international partners to promote condom use, its prevalence remains paradoxically low among the most exposed groups. In university settings, this issue is particularly significant: young adults develop autonomy and explore their sexuality, often without proper guidance or adequate information. Many barriers, cultural, psychological, or institutional, still hinder consistent condom use, despite its proven effectiveness in preventing STIs, HIV/AIDS, and unplanned pregnancies. In this context, it is essential to identify the determinants of condom use (or non-use) to guide prevention policies tailored to the socio-cultural realities of young people in sub-Saharan Africa, particularly in Burundi. Methodology: A cross-sectional, descriptive, and analytical study was conducted in April 2025 at the University of Lake Tanganyika in Burundi. It involved a sample of 196 students selected through non-probability convenience sampling due to the lack of a nominative database. The main objective was to identify sociodemographic, sociocultural, behavioral, and cognitive factors influencing condom use among university students. Data were collected via a structured face-to-face questionnaire covering sexual practices, preventive attitudes, and knowledge of sexual and reproductive health. Data were entered and analyzed using Microsoft Excel and SPSS version 25. Statistical analysis was based on bivariate tests with calculation of Odds Ratios (OR) and 95% Confidence Intervals (CI) to assess the strength and significance of associations between the dependent variable (condom use) and the independent variables. Statistical significance was set at p < 0.05 Results: The prevalence of condom use was 44.4%, with significant determinants identified as place of upbringing (OR = 4.136; p < 0.001), shame in purchasing condoms (OR = 3.009; p < 0.001), knowledge of condom benefits (OR = 5.856; p < 0.001), and knowing someone who died from AIDS (OR = 4.741; p < 0.001). Conclusion: Strengthening communication and education on sexual health is necessary, particularly to break taboos and promote condom use.